2013
DOI: 10.1111/acel.12069
|View full text |Cite
|
Sign up to set email alerts
|

High levels of oncomiR‐21 contribute to the senescence‐induced growth arrest in normal human cells and its knock‐down increases the replicative lifespan

Abstract: Cellular senescence of normal human cells has by now far exceeded its initial role as a model system for aging research. Many reports show the accumulation of senescent cells in vivo, their effect on their microenvironment and its double-edged role as tumour suppressor and promoter. Importantly, removal of senescent cells delays the onset of age-associated diseases in mouse model systems. To characterize the role of miRNAs in cellular senescence of endothelial cells, we performed miRNA arrays from HUVECs of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 54 publications
(79 reference statements)
2
66
0
Order By: Relevance
“…In addition, upregulation of mir-26a, mir-29a and mir-23a (Boon et al ., 2011; Dellago et al ., 2013) has been reported in aging mice and humans. One of the miRNAs showing the highest increase was mir-34b-3p.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, upregulation of mir-26a, mir-29a and mir-23a (Boon et al ., 2011; Dellago et al ., 2013) has been reported in aging mice and humans. One of the miRNAs showing the highest increase was mir-34b-3p.…”
Section: Resultsmentioning
confidence: 97%
“…RTEF-1 targets genes such as VEGF and HIF-1α in endothelial cells under hypoxia and increases vascular relaxation by modulating eNOS (Dellago et al ., 2013; Zhu et al ., 2013). In addition, previous studies have shown that VEGF promoter activity is reduced in aged animals (Rivard et al ., 1999).…”
Section: Resultsmentioning
confidence: 99%
“…miR-23a was previously reported to be upregulated in replicative senescent human umbilical vein endothelial cells and human umbilical cord blood-derived multipotent stem cells (Lee et al ., 2011; Dellago et al ., 2013). In senescent BJ and MC-5 human fibroblast cells, we also observed upregulated miR-23a levels; additionally, a concomitant reduction of TRF2 expression in both mRNA and protein levels was also apparent.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that among several up-regulated miRNA during replicative or premature senescence of normal human endothelial cells was miR-21 (Dellago et al 2013 ). Transfection of miR-21 into early passage cells induced senescence, up-regulation of p21…”
Section: Ink4amentioning
confidence: 99%